Penerapan Forecasting Menggunakan Metode Time Series Untuk Menentukan Proyeksi Sales di Perusahaan Manufacturing Furniture - Prasakti, Lukito Angga; Juliane, Christina (Building of Informatics, Technology and Science (BITS), 2023)
The large population certainly encourages companies, including manufacturing companies, to continue to develop their production both in terms of quality and quantity, especially since the number of companies with the same focus is quite large. This is because, every certain company wants to get a lot of profit and minimal consumer or customer complaints. One way that is considered to be able to overcome this is by carrying out company policy referring to forecasting product sales in the future. Therefore, researchers want to find out more about the application of forecasting to determine monthly sales projections for the following year at a Furniture Manufacturing Company. The aim is to determine the role of forecasting in making policies on the company's production at a later time by considering sales projections based on the company's forecasting results. The method used is time series by collecting data through documentation at the regular local market in 2022 to be precise 12 months. After the data is collected, it will be analyzed in depth so that it is known from the research results that careful forecasting will produce forecasts that are not far from reality and can help in calculating sales projections for furniture manufacturing companies at a later time, with a MAPE value of 0.06